(3GdOhdI GdbGfhfjI hGdfXGe GdSjGSj GdESdGej (B:s (3OQGSI OSJhQjI ebGQfI (B/ s - (3efjQ MejO GdHjGJjs; (3KQhJ HOhjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1976)
(3JHOC gPg GdQSGdI HGdJYQja HGdOhdI GdbGfhfjI hfTCJgG, Ke JfbSe Edi bSejf MjK jJfGhd GdbSe GdChd ebheGJ GdOhdI GdbGfhfjI, hGdbSe GdKGfj Yf VeGfGJ JMbjb GdOhdI GdbGfhfjI Ch NVhY GdOhdI ddbGfhf(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1976.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B499 - 522.s
Keywords: (3GdbGfhf GdOSJhQjs; (3ebheGJ GdOhdI GdbGfhfjIs; (3NVhY GdOhdI ddbGfhfs; (3JOQL GdbhGYO GdbGfhfjIs; (3GdGYJQGa HGdMbhb hGdMQjGJs; (3Mb GdYeds; (3eHOC GdeSGhGI aj GdESdGes; (3fjGHI GdNdjaI Yf GdCeIs; (3JfXje GdQbGHI GdbVGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs